2010
DOI: 10.1175/2009jhm1183.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the JULES Land Surface Model Energy Fluxes Using FLUXNET Data

Abstract: Surface energy flux measurements from a sample of 10 flux network (FLUXNET) sites selected to represent a range of climate conditions and biome types were used to assess the performance of the Hadley Centre land surface model (Joint U.K. Land Environment Simulator; JULES). Because FLUXNET data are prone systematically to undermeasure surface fluxes, the model was evaluated by its ability to partition incoming radiant energy into evaporation and how such partition varies with atmospheric evaporative demand at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 28 publications
2
92
0
Order By: Relevance
“…5b and d which show the mean seasonal cycle of ET(mm month −1 ) and give an approximation of the mean bias per month for each of the models. Similar trends have been observed by Blyth et al (2010), who used surface energy flux measurements from 10 FLUXNET sites around the world that represented a range of climate conditions and biome types, and found that the JULES-base evaporation is higher than that observed; the same results were also found by Van den Hoof et al (2011), who found that the JULES-base latent heat flux is overestimated over cropland in Europe. One possibility for this bias is an overestimation of canopy interception.…”
Section: Resultssupporting
confidence: 85%
“…5b and d which show the mean seasonal cycle of ET(mm month −1 ) and give an approximation of the mean bias per month for each of the models. Similar trends have been observed by Blyth et al (2010), who used surface energy flux measurements from 10 FLUXNET sites around the world that represented a range of climate conditions and biome types, and found that the JULES-base evaporation is higher than that observed; the same results were also found by Van den Hoof et al (2011), who found that the JULES-base latent heat flux is overestimated over cropland in Europe. One possibility for this bias is an overestimation of canopy interception.…”
Section: Resultssupporting
confidence: 85%
“…The Bowen ratio closure method is often adopted to correct the non-closure. It takes on the assumption that the Bowen ratio (ratio of the sensible to the latent heat fluxes) is well estimated by the eddy covariance system, so that the turbulent fluxes can be adjusted while conserving the Bowen ratio to ensure closure (Blyth et al, 2010;Zheng et al, 2014;Er-Raki et al, 2008). The adjusted sensible and latent heat fluxes can be computed as…”
Section: Energy Balance Closurementioning
confidence: 99%
“…Manipulative experiments can also be used to evaluate modeled responses of water and energy to global change ). Data sets from over 100 sites on soil and permafrost data and active layer depths from the Circumpolar Active Layer Mon- Data sets that are often used for benchmarking biogeochemical cycle models include atmospheric CO 2 records on seasonal to centennial time scales (Dargaville et al, 2002;Heimann et al, 1998) and satellite data at seasonal or longer time scales (Blyth et al, 2010;Maignan et al, 2011;Randerson et al, 2009). Other available data sets for biogeochemical cycle benchmarking include global gross primary production (GPP), NPP, soil respiration, ecosystem respiration, plant biomass, litter pool, litter decomposition rates, and soil carbon data products (Table 3).…”
Section: Candidate Benchmarks For Evaluation Of Various Aspects Of Lamentioning
confidence: 99%